On the Origin of Reduced Cytotoxicity of Germanium-Doped Diamond-Like Carbon: Role of Top Surface Composition and Bonding - Zemek, Josef; Jiricek, Petr; Houdkova, Jana; Ledinsky, Martin; Jelinek, Miroslav; Kocourek, Tomas (Nanomaterials (Basel, Switzerland), 2021)
This work attempts to understand the behaviour of Ge-induced cytotoxicity of germanium-doped hydrogen-free diamond-like carbon (DLC) films recently thoroughly studied and published by Jelinek et al. At a low doping level, the films showed no cytotoxicity, while at a higher doping level, the films were found to exhibit medium to high cytotoxicity. We demonstrate, using surface-sensitive methods-two-angle X-ray-induced core-level photoelectron spectroscopy (ARXPS) and Low Energy Ion Scattering (LEIS) spectroscopy, that at a low doping level, the layers are capped by a carbon film which impedes the contact of Ge species with tissue. For higher Ge content in the DLC films, oxidized Ge species are located at the top surface of the layers, provoking cytotoxicity. The present results indicate no threshold for Ge concentration in cell culture substrate to avoid a severe toxic reaction.
Keywords: low energy ion scattering spectroscopy; diamond-like carbon; carbon capping film; germanium; Raman spectroscopy; cytotoxicity; photoelectron spectroscopy